Micro-controller based water level sensing system - Nyamukuwa, Tinotenda (Midlands State University, 2019)
The Micro-controller based water level sensing system is an Arduino based project that was designed to capture water level distances using micro-controllers as the tank fills up or as it is emptied. The system will be used for monitoring the daily operations which involve the filling up of the tanks that feed water to the main boilers which generate electricity. Information about the current system was obtained using questionnaires, interviews and observations. Previously, during each daily shift, water readings were manually measured using a vertical rod and then recorded. When the tank became empty or full, the foreperson would then switch on or of the pumps respectively. Upon doing research there was a need for a system that would perform these repetitive tasks that are boring and monotonous such that forepersons may simultaneously perform other tasks as the system automatically manages the start or stop of pumps. Tank readings captured into the system will presented as reports to the section head of operations which could not be done before hand. Tests including black and white box, unit and acceptance testing were done. Verification and validation of the system was done to ensure that it is functioning as stated in objectives. After all tests were done various maintenance techniques were agreed on such as corrective, adaptive and perfective maintenance. The tools used to develop this system were Arduino, PHP and MySQL database.